THE ROLE OF ENGLISH COMMUNICATION SKILL FOR THE GUEST SERVICE OFFICERS IN HANDLING THE FOREIGN GUESTS TO IMPROVE THE QUALITY OF HUMAN RESOURCE AT A HOTEL - jaenal, jaenal (TEXTURA, 2018)
The title of the research aims to know the role of English Communication Skill for the Guest Service Officers in handling the foreign guests to improve the quality of human resource at a hotel. In this research, the writer used a descriptive method through literature study by collecting some data taken from relevant books or websites. The result of research shows that English communication is really required for the guest service officers because they are the first people in a hotel who should communicate with the guests, including the foreign guests. When the foreign guests come, the guest service officers must use an international language. That is English. It is a must for them to be able to speak English. Last but not least, the writer suggests that the hotels should give the special training for the guest service officers. Therefore, they will feel more confident when they have to face the foreign guests. Indirectly, that English training can improve the quality of human resource that can make the image of hotel better and better.